Budgeting in Albania - Klepsvik, Knut (OECD Publishing, 2014)
The Republic of Albania is located in south-eastern Europe and has a population of 2.8 million (2011 census). It was established as a unitary parliamentary republic in 1991 after 46 years of Communist rule. This review of the budget process of the Republic of Albania was carried out as part of the work programme of the OECD Working Party of Senior Budget Officials. In preparation for the review, a team for the OECD Secretariat led by Knut Klepsvik undertook a mission to Tirana from 29 October to 2 November 2012. The substance of this review is divided into 4 sections which details the budgeting process in Albania and includes an Annex summarising recent budget reviews that have taken place in the country. JEL classification: H50, H61, H83, O21, O52 Keywords: Annual budget, budgetary process, budget structure, fiscal policy, fiscal rules, parliamentary budget, procurement
Keywords: Finance and Investment; Governance; Albania